2016
DOI: 10.1172/jci.insight.89631
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vesicle miRNAs for therapy response monitoring in Hodgkin lymphoma patients

Abstract: BACKGROUND. Cell-free circulating nucleic acids, including 22-nt microRNAs (miRNAs), represent noninvasive biomarkers for treatment response monitoring of cancer patients. While the majority of plasma miRNA is bound to proteins, a smaller, less well-characterized pool is associated with extracellular vesicles (EVs). Here, we addressed whether EV-associated miRNAs reflect metabolic disease in classical Hodgkin lymphoma (cHL) patients.METHODS. With standardized size-exclusion chromatography (SEC), we isolated EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(184 citation statements)
references
References 50 publications
(92 reference statements)
6
175
1
2
Order By: Relevance
“…Although we observed lower levels of miR-21-5p in mixed cellularity compared to nodular sclerosis cHL cell lines, this was not supported by a previous study showing similar miR-21-5p levels in nodular sclerosis and mixed cellularity cell lines and cHL total tissues [18]. More recently, plasma miR-21-5p levels were identified as a potential circulating biomarker in cHL patients [48,49]. A moderate increase in apoptosis has been reported upon miR-21-5p inhibition in L428 cells.…”
Section: Discussioncontrasting
confidence: 98%
“…Although we observed lower levels of miR-21-5p in mixed cellularity compared to nodular sclerosis cHL cell lines, this was not supported by a previous study showing similar miR-21-5p levels in nodular sclerosis and mixed cellularity cell lines and cHL total tissues [18]. More recently, plasma miR-21-5p levels were identified as a potential circulating biomarker in cHL patients [48,49]. A moderate increase in apoptosis has been reported upon miR-21-5p inhibition in L428 cells.…”
Section: Discussioncontrasting
confidence: 98%
“…Further studies will be performed to clarify this data. Van Eijndhoven et al confirmed our results in terms of high levels of EVs in patients with respect to controls [141]. Moreover, we and others reported that plasma EV miRNA levels, including miR155, miR127, miR21, and let7, reflect the presence of the tumor and could be a diagnostic tool for therapy response and relapse monitoring in HL [139,141].…”
Section: Clinical Potential Of Evs As Biomarkers and Therapeuticssupporting
confidence: 87%
“…Serum, plasma, whole blood, nasopharyngeal brushing and frozen tumor biopsy samples were collected and processed for DNA and RNA isolation according to published protocols . Extracellular vesicles (EVs) were isolated from serum and plasma by SEC Sepharose CL‐2B column (GE Healthcare) as described previously . TRIZOL LS (Invitrogen) was used to isolate total RNA from 250 μL total serum or plasma according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%